Urbanismo táctico como estrategia participativa, para la conformación de diseño urbano que impulsen la mitigación de conflictos socio-espaciales en Guadalajara de Buga, Valle del Cauca en la carrera 9 entre calles 13 y 17 - Calderón Toro, Carlos Mario (Universidad Antonio Nariño, 2021)
This thesis performs the analysis of a specific section located in the municipality of Guadalajara de Buga, because it currently presents some socio-spatial conflicts which have negatively modified this area, this happens because currently the inhabitants of the city have specific needs that require attention and have intervened inadequately, Since the urban, road and mobility sectorial plans are established in a general manner and currently there has not been an urban intervention that meets the needs of the population, helping to promote the regulation of land use and at the same time articulate the physical-spatial and urban transformations of the study area, which is Carrera 9 between 13th and 17th Streets.